Implementasi Kebijakan Menteri Kelautan dan Perikanan Nomor 71/Permen-Kp/2016 Tentang Alat Tangkap Purse Seine di PPN Sibolga Provinsi Sumatera Utara - Rizki Mulli Ranto; Hendrik; Hazmi Arief (JURNAL SOSIAL EKONOMI PESISIR, 2021)
The research about Implementation of minister of marine and fisheries regulation Number 71/PERMEN-KP/2016 was carried out from 3 June to 10 June 2020 in PPN Sibolga, North Sumatra Province. The purpose of this study was to find out implementation, fishermen's responses, and problems that arries because this regulation Number 71/PERMEN-KP/2016 about fishing gear purse seine in PPN Sibolga, North Sumatra Province. The research approach used in this study is qualitative approach with Case study metodhs. Data retrival conducted by researchers is by interviews, observation and documentations. While data analysis is done trough three stages, namely data reduction, data presentation and conclusion / verification. The results showed that all respondents studied 100% has been implemented this policy Number 71/PERMEN-KP/2016, almost all of the respondents rejected the policy, and the problems that arrise because of the policy is considered detrimental to fisherman who use vessels under 30 GT.